Analisis Fantasi dalam Harry Potter dan Sastra Tradisional Malin Kundang untuk Meningkatkan Kemampuan Berpikir Kritis - Ismanto Ismanto; Khoirunnisa Nurhanafi; Sigit Rahmawan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Critical thinking skills are important skills that need to be developed in students to face the challenges of 21st century modern fantasy literature such as Harry Potter and traditional literature such as The Legend of Malin Kundang in developing students' critical thinking skills. With David Krech's qualitative narrative approach and social perception theory, it was found that Harry Potter presented complex moral conflicts with universal values, while Malin Kundang taught moral lessons about family relationships and responsibility. This research also proposes a literature-based learning strategy that integrates local and global values to improve students' critical thinking and cultural appreciation.